Optimalisasi Sistem Pemanasan Bahan Bakar MFO Melalui Penerapan Pipa Bypass Exhaust di PLTD Paokmotong - Agra Ananda Vigarya Putra; Yesung Allo Padang (JURNAL KARYA PENGABDIAN TEKNIK MESIN, 2026)
PLTD Paokmotong uses Marine Fuel Oil (MFO) as the main fuel due to its economic advantage; however, MFO requires a reliable heating system to ensure proper operation. Operational constraints occurred due to limited utilization of exhaust gas heat caused by restricted Heat Recovery Thermal Oil (HRTO) system availability, resulting in reduced flexibility of the MFO heating process and increased use of High Speed Diesel (HSD). This community service activity aims to optimize the MFO fuel heating system through the implementation of an exhaust bypass pipe at PLTD Paokmotong. The method employed a technology insemination and appropriate technology upgrade approach, including system observation, exhaust bypass pipe implementation, and operational performance evaluation of the heating system. The results indicate that the exhaust bypass pipe improves the reliability and flexibility of the MFO heating system, accelerates fuel changeover from HSD to MFO, and maintains stable fuel temperature during power plant operation. Keywords : PLTD, MFO, HRTO, exhaust bypass pipe, community service